ADIK PKL ABG SEBUAH MODEL PEMBELAJARAN ACTIVE LEARNING - Firdos Mujahidin (Balai Diklat Keagamaan Bandung, 2021)
The purpose of this research is The purpose of this research is to develop existing model, method, and approach into a new learning model as a series of activities, and it has been commonly practiced in learning. The research method used is Research and Development (R&D) designed by Richey and Klien at the 3rd level. The results showed that the learning model named